A comparative study of different concentrations of pure Zn powder effects on synthesis, structure, magnetic and microwave-absorbing properties in mechanically-alloyed Ni–Zn ferrite. (September 2016) - Hajalilou, Abdollah; Mazlan, Saiful Amri; Shameli, Kamyar
Abstract: In this study, a powder mixture of Zn, Fe2 O3 and NiO was used to produce different compositions of Ni1− x Zn x Fe2 O4 ( x =0.36, 0.5 and 0.64) nanopowders. High-energy ball milling with a subsequent heat treatment method was carried out. The XRD results indicated that for the content of Zn, x =0.64 a single phase of Ni–Zn ferrite was produced after 30 h milling while for the contents of Zn, x =0.36 and 0.5, the desired ferrite was formed after sintering the 30 h-milled powders at 500 °C. The average crystallite size decreased with increase in the Zn content. A DC electrical resistivity of the Ni–Zn ferrite, however, decreased with increase in the Zn content, its value was much higher than those samples prepared by the conventional ceramic route by using ZnO instead of Zn. This is attributed to smaller grains size which were obtained by using Zn. The FT-IR results suggested two absorption bands for octahedral and tetrahedral sites in the range of 350–700 cm −1 . The VSM results revealed that by increasing the Zn content from 0.36 to 0.5, a saturation magnetization reached its maximum value; afterwards, a decrease was observed for Zn with x =0.64. Finally, magnetic permeability and dielectric permittivity were studied by using vector network analyzer to explore microwave-absorbing properties in X-band frequency. The minimum reflection loss value obtained for Ni0.5 Zn0.5 Fe2 O4 samples, about −34 dB at 9.7 GHz, making them the best candidates for high frequency applications. Highlights: Ni–Zn ferrites nanoparticles were synthesized by mechano-thermal method. Effect of Zn content on structural, dielectric and magnetic behaviors was studied. Microwave-absorbing trait in X-band frequency was studied by vector network analyzer. The minimum RL value obtained for Ni0.5 Zn0.5 Fe2 O4 samples; ∼−34 dB at 9.7 GHz.